Strengthening the relationship between community resilience and health emergency communication: a systematic review - Tushna Vandrevala; Elizabeth Morrow; Tracey Coates; Richard Boulton; Alison F. Crawshaw; Emma O'Dwyer; Carrie Heitmeyer (BMC, 2024)
Abstract Background Community resilience and health emergency communication are both crucial in promoting a community's ability to endure crises and recover from emergency events. Yet, a notable gap in theory and evidence exists in the relationship between them. We aim to explore the relationship between community resilience and health emergency communication and to identify strategies and interventions to strengthen their usefulness to each other. Based on the results, a secondary aim was to develop a model of community-centred resilience and health emergency communication. Methods A systematic review of literature published between January 1990 and February 2024 was undertaken following Joanna Briggs Institute guidelines. Electronic databases (Web of Science, Social Science Citation Index, PubMed/MEDLINE) were searched using key terms. Eligibility criteria were developed from the literature and the knowledge of the multidisciplinary team. Inductive thematic analysis generated key themes. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were applied to present the findings. Results The searches identified 300 articles, of which 86 met the inclusion criteria. Two main themes were identified from the literature: (i) the relationship between emergency communication and community resilience, including subthemes: building trust and collaboration within communities, identifying resources and their distribution, tailoring communication strategies, considering inclusion and equity, and community engagement and feedback and (ii) strategies and interventions, including subthemes: facilitating community structures as channels for communication, respecting personal and private boundaries in health communication, targeting outreach for effective crisis communication, building resilience through training and communication initiatives, and demonstrating commitment to equity and inclusion. Conclusions There is a small, yet valuable, body of evidence to demonstrate the value of bolstering community-centred resilience for emergency preparedness, response and recovery. The model of community-centred resilience and health emergency communication developed can inform policy, research and practice. Further research is required to develop and test community-centred approaches to enhance inclusive risk communication and equitable recovery.